Tufted Carpet - Textile Fibers, Dyes, Finishes, and Processes - Woodings, Calvin (Woodhead Publishing Ltd, 2011)
A comprehensive presentation of up-to-date information on the process technology, applications and markets for managing cellulose fibers. For managers, textile technologists, sales and marketing specialists, and all others involved in the successful running of a textile company.